MANAGEMENT OF INCOMING MAIL ARCHIVES AT THE BENGKAYANG SUB-DISTRICT OFFICE BENGKAYANG DISTRICT - Medlin Patricia; Yoseph Erbito (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The Bengkayang Head Sub-District Office, Bengkayang Regency, is one of the community service offices located in Bengkayang Sub-District, Bengkayang Regency, West Kalimantan Province. In government affairs, it is certainly never broken in terms of services and correspondence. The Bengkayang Head Sub-District Office will receive incoming letters every day, both internal and external. These incoming letters must be managed properly by applicable procedures and will eventually be archived. The resources owned also have a big share in carrying out their duties and functions, so what has been planned properly can also be realized properly. This research is descriptive qualitative research. The methods used are observation, interviews, and documentation studies. In this study, researchers made direct observations at the Bengkayang Head Sub-District Office regarding matters relating to the management of incoming letters and up to the stage of storage in the archives. After that, the researcher also interviewed 2 employees who were directly related to these activities, and the researcher also conducted a documentation study to strengthen the results of the data that had been obtained.Based on the results of the research, it can be seen that the management of incoming letter archives at the Bengkayang Head Sub-District Office is still not optimal; the management of incoming letter archives is still not neat, so when the archive is needed, it cannot be found because there is no special archive room. The staff on duty is less competent in carrying out his duties because he is often negligent and leaves the place during working hours. Training in managing archives has also never been given to the staff in charge. Responsibility is given only because the staff is a senior employee. Therefore, the Bengkayang Head Sub-District Office needs to provide training to staff in managing records, especially in terms of correspondence. The archive place should also be provided specifically and managed in accordance with procedures so that it can maintain office archives more optimally and effectively.